High versus low glycemic index 3-h recovery diets following glycogen-depleting exercise has no effect on subsequent 5-km cycling time trial performance - Brown, L. J.S.; Midgley, A. W.; Vince, R. V.; Madden, L. A.; McNaughton, L. R. (Journal of Science and Medicine in Sport, 2013)
Objectives: Some athletes train/compete multiple times in a single day and rapid restoration of muscle and hepatic glycogen stores is therefore important for athletic performance. Design: Randomised, counterbalanced, crossover, single blinded study investigated the effects of low/high glycaemic index (GI) meals on the physiological responses to a 3-h recovery period and subsequent 5-km cycling time trial (TT). Methods: Seven male cyclists completed glycogen-depleting exercise followed by a 3-h recovery period, when participants consumed either a high or low GI meal providing 2 g kg-1 BM of carbohydrate. Participants then performed a 5-km cycling TT. Blood samples were analysed for glucose insulin, free fatty acid (FFA) and triglyceride. Results: There was no significant difference between the median (IQR) cycling TT time of 8.5 (3.0) min in the LGI condition and 8.4 (1.8) min in the HGI condition (p = 0.45). Serum insulin was significantly higher in the HGI condition throughout the 3-h recovery period (p = 0.025), FFA concentrations were higher in the HGI condition only at 30 min into recovery (p = 0.008). The respiratory exchange ratio (p = 0.028) and carbohydrate oxidation rate (p = 0.015) increased over time in the HGI condition, whereas the rate of fat oxidation demonstrated the opposite response (p = 0.001). No significant differences between conditions were observed for any physiological variables at the end of the 5-km TT. Conclusions: Although the GI of the two meals indicated important metabolic differences during the recovery period, there was no evidence suggesting these differences influenced subsequent 5-km TT performance.